2012
DOI: 10.1021/cs200648q
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hierarchical Cerium-Incorporated MFI Zeolite Catalysts for the Catalytic Fast Pyrolysis of Lignocellulosic Biomass

Abstract: We report the synthesis of a new multifunctional mesoporous zeolite catalyst with cerium incorporated within the framework. This catalyst shows a shift in selectivity from typical HZSM-5 products (benzene, toluene, and xylenes) to valuable oxygenated chemicals (furans, ketones, aldehydes) during the catalytic fast pyrolysis of lignocellulosic biomass. The cerium-incorporated hierarchical zeolite was synthesized using a dry-gel method followed by steam-assisted crystallization. The catalyst was characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(53 citation statements)
references
References 41 publications
0
53
0
Order By: Relevance
“…The volume in the pores can prevent repolymerization and coke formation. The acid sites can promote the cleavage of C-O and C-C bonds and catalytic transformation of intermediates through reactions like dealkylation, dehydroxylation, demethoxylation, aromatization, dehydration, cracking, isomerization, and oligomerization (Mullen and Boateng 2010;Neumann and Hicks 2012;Yu et al 2012). Therefore, the relative content of aromatic hydrocarbons increased while the relative content of total phenolic compounds decreased in the catalytic stepwise pyrolysis process.…”
Section: Catalytic Stepwise Pyrolysis Of Lignin With Hzsm-5mentioning
confidence: 99%
See 1 more Smart Citation
“…The volume in the pores can prevent repolymerization and coke formation. The acid sites can promote the cleavage of C-O and C-C bonds and catalytic transformation of intermediates through reactions like dealkylation, dehydroxylation, demethoxylation, aromatization, dehydration, cracking, isomerization, and oligomerization (Mullen and Boateng 2010;Neumann and Hicks 2012;Yu et al 2012). Therefore, the relative content of aromatic hydrocarbons increased while the relative content of total phenolic compounds decreased in the catalytic stepwise pyrolysis process.…”
Section: Catalytic Stepwise Pyrolysis Of Lignin With Hzsm-5mentioning
confidence: 99%
“…Different kinds of catalysts have been adopted in the pyrolysis reactor, such as metal chlorides, metal oxide catalyst, and zeolites (Mullen and Boateng 2010;Neumann and Hicks 2012;Asadieraghi et al 2015;Chen et al 2015b). Zeolites are the most commonly used catalysts in the literature for catalytic pyrolysis of lignin because of their special pore structure and acid sites that can induce oligomerization, dehydration, deoxygenation, demethoxylation, and aromatization reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a large fraction (>90%) of total coke is classified as "soluble" coke, which is continuously thermally disintegrated, especially at reaction temperatures of 500-550 • C [42,43]. The remaining is "insoluble" coke that deposits on the external surface and inside the pores, where strong acidic sites with small apertures or cages exists [35,44]. Thus, in a scaled-up continuous process, much of the soluble coke will be continuously removed from the catalyst surface, ensuring longer catalyst active time before regeneration is required.…”
Section: Solid Product: Char and Cokementioning
confidence: 99%
“…Jeon et al [107] reported that large pore mesoporous material (such as SBA-15, Pt/SBA-15, AlSBA-15, and Pt/AlSBA-15) could promote the pyrolysis of cellulose, hemicellulose, and lignin. It was found that AlSBA-15 had a considerable amount of acid sites that are advantageous for dehydration, cracking, and decarbonylation reactions [107,108].…”
Section: Catalytic Pyrolysis Of Biomassmentioning
confidence: 99%